Etika Bisnis Islam Dalam Transaksi Jual Beli di Pasar Tradisional Ngronggo Kota Kediri - Ihna Nilava; Ahmad Fauzi (Institut Agama Islam Tribakti Kediri, 2020)
Buying and selling activities are the activity of exchanging goods or material ownership permanently. One of the places for buying and selling is the Market. Along with the times of very rapid economic development, business competition is increasingly high. With very high competitors, business people use various methods to get high profits, so business people often ignore Islamic business ethics in running their business. Ethics is a good behavior of human behavior that covers social values. Good ethics includes honesty, reliability, disciplined loyalty. This study analyzes more deeply about Islamic business ethics using qualitative descriptive methods because the data used are through observation, interviews and documentation. In this context the researcher wants to examine the application of Islamic business ethics in the sale and purchase transactions at the Ngronggo Traditional Market in Kediri City. The results of the study of the application of Islamic business ethics in the sale and purchase transactions at the Ngronggo Market in Kediri City, led most of the traders to implement and run Islamic business ethics. although not all traders have adopted Islamic business ethics.